Method for manufacturing printed matter, method for manufacturing laminate using the same, and method for manufacturing packaging bag
Patent Information
- Application Number
- CN202380015636.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-03
- Filing Date
- 2023-02-06
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-02-06
AI Technical Summary
When printing on flexible polyolefin film, there are problems such as insufficient registration accuracy and easy tearing of packaging bags, especially in roll-to-roll printing, where ink cohesion causes film position displacement and insufficient registration accuracy.
The ink is transferred onto a polyolefin film with a tensile modulus of 200 MPa to 1,000 MPa in the MD direction using a center imprinting printing method. The ink is then cured by electron beam irradiation under an accelerating voltage of 110 kV and an irradiation dose of 40 kGy. At the same time, inks containing specific components and surface treatment processes are used to improve the film's tension and adhesion.
It achieves excellent registration accuracy even when using soft polyolefin films, effectively suppresses bag breakage, and improves the overall quality of printed materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing printed matter, a laminated body using the same, and a method for manufacturing packaging bags. Background Technology
[0002] To add patterns to packaging materials for food and hygiene products, various printing methods are widely used, including gravure printing, flexographic printing, offset printing, inkjet printing, screen printing, and roller coating. Gravure and flexographic printing are particularly common for flexible packaging materials using plastic film. However, gravure and flexographic printing typically use inks containing solvents and water, leading to increased emissions of VOCs and carbon dioxide during the drying process, raising concerns about environmental impact.
[0003] Therefore, in recent years, the use of active energy line curable printing inks, which can be instantly cured by irradiation with active energy lines such as electron beams and ultraviolet light, has been developed. Previously, in offset printing, a common method for printing on paper, the following solutions were proposed to improve adhesion to plastic films: an active energy line curable offset printing ink composition, characterized by containing a photopolymerization initiator and a compound having an olefinic unsaturated bond, and further containing 8% to 12% by mass of a sensitizing compound with a specific structure; a method for manufacturing a printed material, comprising a printing step of offset printing on a resin film using the aforementioned active energy line curable offset printing ink composition and a curing step of irradiating the resin film after the aforementioned printing step with active energy lines (for example, see Patent Document 1); an active energy line curable composition, characterized by containing (methyl)propyl One or more active energy line polymerizable compounds of methacryloyl groups, wherein (1) the concentration of (meth)acryloyl groups in the composition is in the range of 0.5 or more and less than 2.2 mmol / g, and (2) the indentation elastic modulus of the cured coating is in the range of 100 or more and less than 1,000 MPa; a method for manufacturing an ink-cured product, characterized in that offset printing is performed using the aforementioned ink, and the printed ink is cured using active energy lines (for example, see Patent Document 2); a method for manufacturing a printed product, comprising, in the method of manufacturing a printed product by printing ink onto a film, using a film with a nitrogen concentration of 0.5 to 10.0 atomic% on the surface of the film and irradiating it with active energy lines after printing (for example, see Patent Document 3); and so on.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-168730
[0007] Patent Document 2: Japanese Patent Application Publication No. 2020-33465
[0008] Patent Document 3: International Publication No. 2018 / 163941 Summary of the Invention
[0009] The problem that the invention aims to solve
[0010] In recent years, with the expansion of flexible packaging materials, there has been a demand for packaging materials made of more flexible plastic films. Especially when printing on flexible films such as polyolefin films using conventional roll-to-roll methods, the tension that can be applied to the film is limited, leading to issues such as film misalignment due to ink cohesion and insufficient registration accuracy. On the other hand, if a stiffer film is chosen to improve registration accuracy, the packaging bags become more prone to tearing when used as packaging bags.
[0011] Therefore, the object of the present invention is to provide a method for manufacturing printed matter that can produce printed matter with excellent registration accuracy and suppress bag breakage, even when using a soft film such as a polyolefin film.
[0012] Methods for solving problems
[0013] The present invention, which addresses the aforementioned problems, has the following configuration. That is,
[0014] (1) A method for manufacturing printed matter, comprising in sequence: a transfer printing step, wherein ink is transferred onto a polyolefin film having a tensile elastic modulus of 200 MPa or more and 1,000 MPa or less in the MD direction by a center pressing printing method; and a curing step, wherein the ink is cured by irradiating it with an electron beam.
[0015] (2) The method for manufacturing printed matter as described in (1), wherein the thickness of the aforementioned polyolefin film is more than 20 μm and less than 60 μm.
[0016] (3) The method for manufacturing printed matter as described in (1) or (2), wherein the ratio (C2 / C1) of the crystallinity C2 of the polyolefin film after electron beam irradiation under the conditions of accelerating voltage 110 kV and irradiation dose 40 kGy is 0.8 or more and 1.2 or less.
[0017] (4) The method for manufacturing printed matter as described in any one of (1) to (3), wherein the crystallinity C2 of the aforementioned polyolefin film after electron beam irradiation under the conditions of accelerating voltage of 110 kV and irradiation dose of 40 kGy is more than 20% and less than 50%.
[0018] (5) The method for manufacturing printed matter as described in any one of (1) to (4), wherein the aforementioned polyolefin film contains 10% by mass or more of a polyethylene resin.
[0019] (6) The method for manufacturing printed matter as described in (5), wherein the aforementioned polyolefin film further contains less than 90% by mass of a polypropylene resin.
[0020] (7) The method for manufacturing printed matter as described in any one of (1) to (6), wherein the content of the crystal nucleating agent in the aforementioned polyolefin film is 0.01% by mass or less.
[0021] (8) A method for manufacturing printed matter as described in any one of (1) to (7), wherein, in the aforementioned curing step, electron beam irradiation is performed under conditions of an accelerating voltage of 70 kV or more and 90 kV or less and an irradiation dose of 20 kGy or more and 60 kGy or less.
[0022] (9) A method for manufacturing printed matter as described in any one of (1) to (8), wherein the ink comprises an anionic surfactant.
[0023] (10) A method for manufacturing a printed matter as described in any one of (1) to (9), wherein the ink comprises urethane (meth)acrylate.
[0024] (11) A method for manufacturing printed matter as described in any one of (1) to (10), wherein, in the aforementioned transfer process, ink is transferred by lithographic printing.
[0025] (12) A method for manufacturing a laminate, comprising the steps of manufacturing a printed matter by any one of (1) to (11) and laminating an unstretched polyolefin film onto the printed matter.
[0026] (13) The method for manufacturing the laminate as described in (12), wherein the tensile elastic modulus of the aforementioned unstretched polyolefin film is 50 MPa or more and 400 MPa or less.
[0027] (14) The method for manufacturing a laminate as described in (12) or (13), wherein the thickness of the aforementioned unstretched polyolefin film is 30 μm or more and 100 μm or less.
[0028] (15) A method for manufacturing a packaging bag, comprising, in sequence: a step of manufacturing a laminated body by any one of the laminated body manufacturing methods (12) to (14); and a step of making a bag from the laminated body.
[0029] Invention Effects
[0030] According to the method for manufacturing printed materials of the present invention, even when using a soft film such as a polyolefin film, it is possible to obtain printed materials with excellent registration accuracy and the ability to suppress bag breakage. Detailed Implementation
[0031] The preferred embodiments of the method for manufacturing printed materials according to the present invention will be described in detail below. However, the present invention is not limited to the embodiments illustrated below, and various modifications can be made according to the purpose and use without departing from the spirit of the present invention.
[0032] The method for manufacturing printed matter according to embodiments of the present invention sequentially includes: a transfer printing step, wherein ink is transferred onto a polyolefin film having a tensile modulus of elasticity of 200 MPa to 1,000 MPa in the MD direction by a center-press printing method (hereinafter sometimes simply referred to as the "transfer printing step"); and a curing step, wherein the aforementioned ink is cured by irradiating it with an electron beam (hereinafter sometimes simply referred to as the "curing step"). The ink transferred to the polyolefin film in the transfer printing step can be cured in a short time in the curing step, reducing environmental impact. Prior to the transfer printing step, a surface treatment step, such as corona discharge treatment, may also be performed on the surface of the polyolefin film.
[0033] First, the transfer printing process will be explained. In the transfer printing process, ink is transferred onto a polyolefin film with a tensile modulus of elasticity of 200 MPa to 1,000 MPa in the MD direction by a center-press printing method.
[0034] Center-press printing refers to a printing method where all printing units share a common impression cylinder. Essentially, center-press printing is a wet-on-wet printing method where the ink is cured after full-color printing. Pressure is applied by the rubber blanket of the rear cylinder while the ink transferred to the substrate is still uncured. This reduces the surface roughness of the ink film, suppresses diffuse light reflection, and allows for high ink density with a small amount of ink, resulting in excellent resistance to ink smudging. Furthermore, the short distance between color units during printing improves registration accuracy.
[0035] In this invention, a polyolefin film, which is a flexible film, is used as the printed material. Examples of polyolefin films include unstretched polypropylene film, biaxially stretched polypropylene film, unstretched polyethylene film, and biaxially stretched polyethylene film. Among these, unstretched polyolefin film is preferred, and unstretched polypropylene film is more preferred, as it is easier to make the tensile modulus of elasticity fall within the range described later.
[0036] The present invention is characterized by using a polyolefin film with a tensile modulus of elasticity in the MD direction (flow direction) of 200 MPa to 1,000 MPa. In the transfer printing process, high tension is typically applied to the printed material in the MD direction to suppress relaxation of the printed material and positional shift of the ink during transfer. Therefore, in the present invention, the tension in the MD direction is based on the tensile modulus of elasticity of the polyolefin film in the MD direction. If the tensile modulus of elasticity in the MD direction is less than 200 MPa, positional shift of the polyolefin film is likely to occur, resulting in decreased registration accuracy. The tensile modulus of elasticity in the MD direction is preferably 400 MPa or more, more preferably 600 MPa or more. On the other hand, if the tensile modulus of elasticity in the MD direction is greater than 1,000 MPa, the packaging bag is prone to breakage during processing.
[0037] Here, the tensile modulus of elasticity in the MD direction of the polyolefin film can be determined according to JIS K7161-1:2014 and JIS K7127:1999. More specifically, a 15mm wide strip of test piece is subjected to tensile testing in the MD direction using a Tensilon universal testing machine with a chuck distance of 50mm and a testing speed of 300mm / min. The tensile modulus of elasticity is determined from the stress-strain curve. Five test pieces are measured, and the average value is taken as the tensile modulus of elasticity in the MD direction of the polyolefin film.
[0038] The tensile modulus of elasticity in the MD direction of polyolefin films tends to increase with higher MD stretch ratios and also tends to increase with heat treatment. Therefore, the tensile modulus of elasticity can be adjusted to a desired range by stretching, heat treatment, or appropriate adjustment of the conditions, as needed. Furthermore, various companies offer polyolefin films with different tensile moduli of elasticity, allowing selection of polyolefin films with the desired tensile modulus of elasticity. Unstretched polyolefin films are particularly preferred, and unstretched polypropylene films are more preferred.
[0039] The thickness of the polyolefin film is preferably 20 μm or more, as its high strength allows for improved registration accuracy. On the other hand, the thickness of the polyolefin film is preferably 60 μm or less, which results in a more flexible print.
[0040] Polyolefins are crystalline resins, and polyolefin films possess a certain degree of crystallinity. In this invention, polyolefin films with minimal changes in crystallinity caused by electron beam irradiation are preferred. Specifically, when the crystallinity of the polyolefin film used in the transfer process is set as C1 [%], and the crystallinity after electron beam irradiation of the polyolefin film under accelerating voltage of 110 kV and irradiation dose of 40 kGy is set as C2 [%], the ratio of the crystallinity C2 after electron beam irradiation to the crystallinity C1 before electron beam irradiation (C2 / C1) is preferably 0.8 to 1.2 or less. For the polyolefin film, a certain tension is applied in the MD direction during the transfer process, and it is irradiated with an electron beam used to cure the ink during the curing process described later. It is anticipated that the crystallinity of the polyolefin will change due to electron beam irradiation. The closer the ratio of crystallinity before and after electron beam irradiation (C2 / C1) is to 1, the better the reduction in strength and brittleness caused by changes in crystallinity can be suppressed. In this invention, an accelerating voltage of 110 kV and an irradiation dose of 40 kGy are selected as conditions to fully exhibit the changes in crystallinity that can be produced by electron beam irradiation. If C2 / C1 is 0.8 or higher, the decrease in strength caused by the decrease in crystallinity can be suppressed, thereby further improving the registration accuracy. On the other hand, if C2 / C1 is 1.2 or lower, embrittlement caused by the increase in crystallinity can be suppressed, thereby further suppressing bag breakage during processing into packaging bags.
[0041] Furthermore, the C2 content of the polyolefin film is preferably 20% or more and 50% or less. If the C2 content is 20% or more, the decrease in strength caused by the decrease in crystallinity during the subsequent curing process can be suppressed, thereby further improving the registration accuracy. On the other hand, if the C2 content is 50% or less, the embrittlement caused by the increase in crystallinity during the subsequent curing process can be suppressed, thereby further suppressing bag breakage during processing into packaging bags.
[0042] Here, the crystallinity C1 and C2 of the polyolefin film can be determined by X-ray diffraction. First, rectangular test pieces (25 mm × 15 mm in orientation of each side) are collected from the polyolefin film after electron beam irradiation at an accelerating voltage of 110 kV and an irradiation dose of 40 kGy, respectively, for C1. The obtained test pieces are attached to the aluminum sample holder of the X-ray diffraction apparatus with the film thickness direction corresponding to the normal direction of the sample holder surface. While changing the incident angle of the X-rays, the diffraction peaks are measured by reflection using a 2θ-θ continuous scan. The measurement conditions are as follows: five points are randomly selected from the test pieces for measurement.
[0043] • Measurement range (2θ): 5–60°
[0044] • Measurement step size (2θ): 0.05°
[0045] • Cumulative time: 2 seconds.
[0046] Next, for the obtained diffraction peaks, the peaks from the crystalline component and the peaks from the amorphous component are separated using analytical software. The crystallinity is calculated from the respective peak areas, and their average value is calculated. The crystallinity [%] can be calculated by multiplying the peak area of the crystalline component by 100 and then dividing by the peak area of the amorphous component. There are no particular restrictions on the analytical software as long as it can separate the target peak; for example, JADE 5.0 and JADE 2010 (MDI Corporation) can be used.
[0047] The polyolefin film of the present invention preferably contains 10% by mass or more of a polyethylene-based resin. Compared with polypropylene, the increase in crystallinity caused by electron beam irradiation is suppressed in polyethylene; therefore, by containing 10% by mass or more of a polyethylene-based resin, the change in crystallinity caused by electron beam irradiation can be reduced. On the other hand, the content of the polyethylene-based resin is preferably 80% by mass or less, which allows the tensile modulus of elasticity to be easily adjusted to the aforementioned preferred range. The content of the polyethylene-based resin is more preferably 50% by mass or less.
[0048] The polyolefin film of the present invention preferably further contains 90% by mass or less of a polypropylene-based resin. By containing 90% by mass or less of a polypropylene-based resin, the change in crystallinity caused by electron beam irradiation can be reduced. The tensile modulus of elasticity can be easily adjusted to the aforementioned preferred range. On the other hand, the content of the polypropylene-based resin is preferably 20% by mass or more, which makes it easy to adjust the tensile modulus of elasticity to the aforementioned preferred range. The content of the polyethylene-based resin is more preferably 50% by mass or more. It should be noted that when the content of the polyethylene-based resin is 50% by mass or more and the content of the polypropylene-based resin is 50% by mass or less, in order to make the tensile modulus of elasticity of the film within the aforementioned range, it is preferable to subject the polyolefin film to uniaxial or biaxial stretching.
[0049] Furthermore, the content of the nucleating agent in the polyolefin film of the present invention is preferably 0.01% by mass or less. Nucleating agents are generally used to improve the crystallinity of the film, but in the present invention, by keeping its content at 0.01% by mass or less, the change in crystallinity caused by electron beam irradiation can be reduced. Particularly when the content of polypropylene resin is high, from the viewpoint of minimizing the change in crystallinity caused by electron beam irradiation, it is preferable to have no nucleating agent present.
[0050] Examples of crystal nucleating agents include those that use inorganic particles such as silica and talc, rosin-based metal salts as main components, sorbitol-based crystal nucleating agents, and crystal nucleating agents formed from aromatic organophosphate metal salts.
[0051] As a measure to address recent environmental problems and achieve carbon neutrality, the polyolefin membrane of the present invention preferably includes recycled raw materials. It should be noted that the recycled raw materials can be those recovered through physical recycling or those recovered through chemical recycling, without particular limitation. Furthermore, it may also include raw materials of biomass origin (plant origin), and is preferably used in combination with conventional petrochemical-derived raw materials.
[0052] The surface of the polyolefin film is preferably treated with a surface treatment such as corona discharge treatment, which can improve the wetting tension of the film surface. A pre-treated polyolefin film can be used, or a surface treatment process such as corona discharge treatment can be performed on the surface of the polyolefin film before the transfer process. Examples of atmospheric gases used during corona discharge treatment include air, carbon dioxide, and nitrogen, or two or more of these can be used.
[0053] Methods for transferring ink onto polyolefin films include offset printing, letterpress printing, and gravure printing. Among these, offset printing is preferred because it is suitable for high-speed printing.
[0054] In offset printing, there are methods using a printing plate without a horizontal plate and methods using a printing plate with a horizontal plate. In this invention, the method using a printing plate without a horizontal plate is preferred. In the method using a printing plate without a horizontal plate, since wetting water is not used during printing, free radicals can be stably generated by electron beam irradiation in the curing process described later. Therefore, the ink can be fully cured, improving the adhesion between the ink and the polyolefin film.
[0055] The ink used in this invention is preferably an electron beam-cured printing ink that is cured by electron beam irradiation in the curing process described later, and preferably contains acrylic resin, pigment, and polyfunctional (meth)acrylate. Here, "(meth)acrylate" is a general term for acrylates and methacrylates. Moreover, it is preferable to contain urethane (meth)acrylate and monofunctional (meth)acrylate.
[0056] The acrylic resin preferably has olefinic unsaturated groups and carboxyl groups. From the viewpoint of improving pigment dispersibility and reducing ink cohesion, thereby further improving registration accuracy, the weight-average molecular weight of the acrylic resin is preferably 5,000 or more, more preferably 15,000 or more. On the other hand, from the viewpoint of suppressing molecular chain complexation and reducing ink cohesion, thereby further improving registration accuracy, the weight-average molecular weight of the acrylic resin is preferably 40,000 or less.
[0057] The acrylic resin content in the ink is preferably 6% by mass or more, and preferably 15% by mass or less.
[0058] Examples of pigments include inorganic pigments and organic pigments. Examples of inorganic pigments include titanium dioxide and carbon black, while examples of organic pigments include phthalocyanine pigments, soluble azo pigments, insoluble azo pigments, and lake pigments. Pigments may also contain two or more of these types.
[0059] The pigment content in the ink is preferably 10% by mass or more, and preferably 50% by mass or less.
[0060] Polyfunctional (meth)acrylates refer to polyfunctional (meth)acrylates with a molecular weight of less than 5,000 and having multiple (meth)acryloyl groups. The molecular weight of polyfunctional (meth)acrylates is preferably less than 1,000. Due to their excellent pigment dispersibility and improved resistance to ink smudging, pentaerythritol trimethacrylate, diglycerol trimethacrylate, bis(trimethylolpropane)trimethacrylate, tricyclodecanediethanol diacrylate, trimethylolpropane EO-modified triacrylate, and bis(pentaerythritol)hexaacrylate are preferred.
[0061] Uraffinate (meth)acrylates refer to (meth)acrylates containing urethane bonds, preferably oligomers with a weight average molecular weight of 2,000 or more and less than 5,000. In this invention, even (meth)acrylates containing one or more (meth)acryloyl groups are classified as urethane (meth)acrylates simply because they contain urethane bonds. The hydrogen bonds between the urethane bonds in urethane (meth)acrylates form hard segments, which impart toughness to the ink-cured film and also bond firmly to the surface of the plastic film, thus improving adhesion to polyolefin films. In addition, the polyol residues in urethane (meth)acrylates form soft segments, which impart flexibility to the ink-cured film, thus further suppressing bag breakage during processing into packaging bags.
[0062] The content of urethane (meth)acrylate in the ink is preferably 5% by mass or more, which can better suppress bag breakage during processing into packaging bags. On the other hand, the content of urethane (meth)acrylate in the ink is preferably 15% by mass or less, which can further improve registration accuracy.
[0063] Monofunctional (meth)acrylates act as additives to reduce ink cohesion, thereby improving registration accuracy.
[0064] Monofunctional (meth)acrylates refer to compounds with a molecular weight of less than 5,000 and containing one (meth)acryloyl group. Examples include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, nonyl methacrylate, decyl methacrylate, undecyl methacrylate, dodecyl methacrylate, tridecyl methacrylate, tetradecyl methacrylate, pentadecyl methacrylate, hexadecyl methacrylate, heptadecanyl methacrylate, octadecyl methacrylate, nonadecanyl methacrylate, eicosyl methacrylate, dodecyl methacrylate, and dodecyl methacrylate. Esters, such as isopropyl methacrylate, isobutyl methacrylate, isoamyl methacrylate, isohexyl methacrylate, isoheptyl methacrylate, isooctyl methacrylate, isononyl methacrylate, isodecyl methacrylate, isoundecyl methacrylate, isododecyl methacrylate, isotridecyl methacrylate, isotetradecyl methacrylate, isopentadecanyl methacrylate, isohexadecyl methacrylate, isoheptadecyl methacrylate, isooctadecyl methacrylate, isononadecanyl methacrylate, isoeicosyl methacrylate, isotidecyl methacrylate, and isotidecyl methacrylate. Two or more of these may also be present. Preferably, alkyl methacrylates have an aliphatic skeleton with 13 to 22 carbon atoms.
[0065] Compared to 100 parts by mass of polyfunctional (meth)acrylate, the content of monofunctional (meth)acrylate in the ink is preferably 1 part by mass or more. This moderately promotes phase separation and facilitates the stable formation of a microphase separation structure, thereby further improving registration accuracy. Conversely, the content of monofunctional (meth)acrylate is preferably 7 parts by mass or less. This moderately suppresses phase separation and facilitates the stable maintenance of the microphase separation structure, thereby further improving registration accuracy.
[0066] The ink used in this invention preferably also contains a surfactant. By containing a surfactant, the dispersibility of the pigment can be improved, thereby further reducing the cohesive force of the ink and further improving the registration accuracy.
[0067] When the ink used in this invention is white ink, anionic surfactants are preferred as surfactants, which can improve the dispersibility of white pigments such as titanium dioxide, zinc oxide, and alumina white, thereby further reducing ink cohesion and improving registration accuracy.
[0068] Examples of anionic surfactants include BYK Japan Co., Ltd.'s "Disperbyk" (registered trademark) 111 (trade name), Daiichi Kogyo Pharmaceutical Co., Ltd.'s "Aqualon" (registered trademark) AR-10 (trade name), sodium dodecylbenzenesulfonate, sodium laurylate, sodium myristate, sodium palmitate, sodium stearate, sodium oleate, potassium laurylate, potassium myristate, potassium palmitate, potassium stearate, potassium oleate, sodium N-stearoyl-L-glutamate, sodium N-stearoyl-N-methyltaurate, and sodium N-lauroyl-L-glutamate. Two or more of these surfactants may also be present.
[0069] The content of surfactant in the ink is preferably more than 1 part by mass and less than 20 parts by mass relative to 100 parts by mass of pigment.
[0070] The ink used in this invention may also contain other components.
[0071] In the transfer printing process, the thickness of the ink transferred onto the polyolefin film is preferably 0.1 to 50 μm. If the ink thickness is 0.1 mm or more, it is easier to transfer the ink evenly onto the film surface, which can improve the printing quality. On the other hand, if the ink thickness is less than 50 μm, the adhesion between the ink and the film will not decrease.
[0072] When transferring white ink onto a substrate, it is preferable to transfer the white ink two or more times. This improves contrast, reduces the amount of ink transferred per transfer, and further enhances registration accuracy.
[0073] Next, the curing process will be explained.
[0074] When an electron beam is irradiated onto the ink transferred onto a polyolefin film, free radicals are generated in the ink, causing it to solidify and produce a printed product. The electron beam passing through the ink also acts on the surface of the polyolefin film, thus generating free radicals thereas as well. It is believed that these free radicals on the surface of the polyolefin film facilitate cross-linking reactions between the ink and the film surface, thereby further enhancing the adhesion between the ink and the polyolefin film in the printed product.
[0075] In the curing process, it is preferable to irradiate the polyolefin film with an electron beam such that the crystallinity of the cured polyolefin film is 20% to 50%. If the crystallinity of the cured polyolefin film is 20% or more, the decrease in strength caused by the decrease in crystallinity can be suppressed, thereby further improving the registration accuracy. On the other hand, if the crystallinity of the cured polyolefin film is 50% or less, the embrittlement caused by the increase in crystallinity can be suppressed, thereby further suppressing the breakage of bags during processing into packaging bags.
[0076] Regarding the crystallinity of the cured polyolefin film, there is a tendency that the higher the electron beam irradiation conditions such as accelerating voltage and irradiation amount, the higher the crystallinity. For example, by selecting a polyolefin film with C1 within the desired range, and by appropriately adjusting the electron beam irradiation conditions such as accelerating voltage and irradiation amount, the crystallinity of the cured polyolefin film can be adjusted to the desired range.
[0077] In the curing process, the accelerating voltage of electron beam irradiation is preferably 70kV or higher and 90kV or lower, and the irradiation dose is preferably 20kGy or higher and 60kGy or lower. By setting the accelerating voltage to 70kV or higher, the ink curing is sufficiently carried out, and the adhesion between the ink and the polyolefin film is further improved. Furthermore, bag breakage during processing into packaging bags is more effectively suppressed. On the other hand, by setting the accelerating voltage to 90kV or lower, the change in crystallinity of the polyolefin film during the curing process can be easily adjusted to the aforementioned preferred range, further improving registration accuracy and suppressing bag breakage during processing into packaging bags. Furthermore, by setting the irradiation dose to 20kGy or higher, the ink curing is sufficiently carried out, further improving the adhesion between the ink and the polyolefin film. An irradiation dose of 30kGy or higher is more preferable. Furthermore, bag breakage during processing into packaging bags is more effectively suppressed. On the other hand, by setting the irradiation dose to 60kGy or lower, the change in crystallinity of the polyolefin film during the curing process can be easily adjusted to the aforementioned preferred range, further improving registration accuracy and suppressing bag breakage during processing into packaging bags.
[0078] The printed matter obtained by the method of the present invention is preferably used in laminates with sealing layers and various packaging bags.
[0079] Next, the method for manufacturing the laminate of the present invention will be described.
[0080] The method for manufacturing the laminate of the present invention includes a step of laminating an unstretched polyolefin film onto a printed material obtained by the aforementioned method. Preferably, the unstretched polyolefin film is laminated on the ink side of the printed material. The laminate is a combination of the printed material obtained by the aforementioned method and the unstretched polyolefin film, wherein the unstretched polyolefin film functions as a sealing layer. Examples of unstretched polyolefin films include unstretched low-density polyethylene film, unstretched medium-density polyethylene film, unstretched high-density polyethylene film, unstretched linear low-density polyethylene film, and unstretched polypropylene film.
[0081] The tensile modulus of the unstretched polyolefin film is preferably 50 MPa or more and 400 MPa or less. If the tensile modulus is 50 MPa or more, bag breakage during processing into packaging bags can be more effectively suppressed. On the other hand, if the tensile modulus is 400 MPa or less, bag making can be performed more easily. The tensile modulus of the unstretched polyolefin film can be measured in the same manner as that of the aforementioned polyolefin film.
[0082] The thickness of the laminated unstretched polyolefin film is preferably 30 μm to 100 μm. A thickness of 30 μm or more further reduces the risk of bag breakage during processing into packaging bags. Additionally, moisture resistance is improved. On the other hand, a thickness of 100 μm or less facilitates bag making.
[0083] Next, the method for manufacturing the packaging bag of the present invention will be described.
[0084] The method for manufacturing the packaging bag of the present invention preferably includes a step of producing a laminated body by the aforementioned method and then forming a bag from the laminated body. As an example of forming a bag from the laminated body, a method of heat-sealing the peripheral portions of two unstretched polyolefin films of the laminated body together can be cited. Specifically, after overlapping two laminated bodies with unstretched polyolefin films facing each other, the peripheral portions in three directions are heat-sealed. After filling with contents, the remaining opening is heat-sealed to form a packaging bag.
[0085] Example
[0086] The present invention will now be described in detail through examples. However, the present invention is not limited to these examples. First, the raw materials used in the various embodiments and comparative examples are shown.
[0087] <Ink Raw Materials>
[0088] Pigment 1: "TIPAQUE" (registered trademark) CR58-2 (manufactured by Ishihara Sangyo Co., Ltd.)
[0089] Pigment 2: Carmine 6B 1483LT (manufactured by Dainippon Seika Co., Ltd.)
[0090] Acrylic resin: 0.55 equivalents of glycidyl methacrylate are reacted with the carboxyl groups of a copolymer comprising 25% by mass methyl methacrylate, 25% by mass styrene, and 50% by mass methacrylic acid to obtain an acrylic resin having olefinic unsaturated groups and hydrophilic groups. The resulting resin has a weight-average molecular weight of 34,000, an acid value of 105 mg KOH / g, and an iodine value of 2.0 mol / kg.
[0091] Multifunctional (meth)acrylate 1: A mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate. "Miramer" (registered trademark) M340 (manufactured by MIWON) Molecular weight 298
[0092] Multifunctional (meth)acrylate 2: Trimethylolpropane EO-modified triacrylate (manufactured by MIWON, "Miramer" (registered trademark) M3190) Molecular weight 692
[0093] Multifunctional (meth)acrylate 3: Dipentaerythritol hexaacrylate (manufactured by MIWON, "Miramer" (registered trademark) M600) Molecular weight 578
[0094] Carbamate (meth)acrylate 1: Carbamate (meth)acrylate containing alicyclic diisocyanate (hydrogenated XDI), carboxylic acids (isophthalic acid and adipic acid), polyols and 2-hydroxyethyl acrylate, with a carbamate bond fraction of 8% by mass and a weight average molecular weight (Mw) of 3,600.
[0095] 2: Polyester-based urethane acrylate (manufactured by Kyoeisha Chemical Co., Ltd., UF-3007M) with a weight-average molecular weight (Mw) of 3,800.
[0096] Monofunctional (meth)acrylates: Octadecyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) Molecular weight 325, melting point 28°C
[0097] Surfactant 1: "Disperbyk" (registered trademark) 111 (manufactured by BYK Japan Co., Ltd.) anionic surfactant
[0098] Surfactant 2: "Aqualon" (registered trademark) AR-10 (Daiichi Kogyo Pharmaceutical Co., Ltd.) is an anionic surfactant.
[0099] <Membrane Production>
[0100] Polyethylene, polypropylene, and additives are mixed in a specified ratio and melt-extruded at 280°C. The mixture is then discharged as a sheet from a die with a slit-shaped outlet and cooled on a cooling roller at a surface temperature of 30°C to obtain an unstretched polyolefin film. Next, the unstretched polyolefin film is preheated as needed and stretched 5 times its length in the longitudinal direction at 135°C to obtain a uniaxially stretched polyolefin film. Then, the uniaxially stretched film is stretched 10 times its width in a tenter frame heated to 160°C as needed, and then heat-treated at 150°C with a permissible relaxation in the width direction to obtain a biaxially stretched polyolefin film.
[0101] The tensile modulus of elasticity and film thickness were determined by the method described later.
[0102] Polyolefin film 1: Tensile modulus of elasticity in the MD direction is 754 MPa, film thickness is 25 μm, polypropylene ratio is 95% by mass, polyethylene ratio is 5% by mass, and crystal nucleating agent ratio is 0.05% by mass.
[0103] Polyolefin membrane 2: Tensile modulus of elasticity in the MD direction is 949 MPa, membrane thickness is 25 μm, polypropylene ratio is 100% by mass, and crystal nucleating agent ratio is 0.00% by mass.
[0104] Polyolefin film 3: tensile modulus of elasticity in the MD direction 488 MPa, film thickness 25 μm, polypropylene ratio 80% by mass, polyethylene ratio 20% by mass, crystal nucleating agent ratio 0.05% by mass.
[0105] Polyolefin membrane 4: Tensile modulus of elasticity in the MD direction 250 MPa, membrane thickness 25 μm, polypropylene ratio 20% by mass, polyethylene ratio 80% by mass, crystal nucleating agent ratio 0.05% by mass.
[0106] Polyolefin film 5: Tensile modulus of elasticity in the MD direction is 184 MPa, film thickness is 25 μm, polypropylene ratio is 10% by mass, polyethylene ratio is 90% by mass, and crystal nucleating agent ratio is 0.05% by mass.
[0107] Polyolefin film 6: tensile modulus of elasticity in the MD direction is 1,230 MPa, film thickness is 25 μm, polypropylene ratio is 100% by mass, and crystal nucleating agent ratio is 0.05% by mass.
[0108] Polyolefin film 7: Tensile modulus of elasticity in the MD direction is 215 MPa, tensile modulus of elasticity in the TD direction is 234 MPa, film thickness is 60 μm, unstretched polypropylene film.
[0109] <Ink Production>
[0110] The acrylic resin, polyfunctional (meth)acrylate, monofunctional (meth)acrylate, urethane (meth)acrylate, and surfactant listed in Table 1 were weighed separately. While stirring with a dispersing blade at 500 rpm, the mixture was heated at 95°C for 390 minutes to obtain a varnish. The pigments listed in Table 1 were added to the obtained varnish, and the mixture was passed through an EXAKT (registered trademark) M-80S three-roll mill (manufactured by EXAKT Corporation) five times at a gap of 1 to obtain offset printing inks, namely red ink and white inks 1 to 7.
[0111] [Table 1]
[0112]
[0113] Next, the evaluation method is shown.
[0114] <Tension elastic modulus of membrane>
[0115] Long strip-shaped test pieces with a width of 15 mm and a length of 60 mm were collected from the aforementioned membranes 1 to 7. Tensile testing was performed using a tensile testing machine (Orientec universal testing machine "Tensilon" (registered trademark)) according to JIS K7161-1:2014 and JIS K7127:1999 "Plastics - Determination of tensile properties" and "Plastics - Test methods for tensile properties," respectively. The tests were conducted at a temperature of 23°C, a chuck distance of 50 mm, and a speed of 300 mm / min, in the mechanical direction (MD direction) of the membrane. The tensile modulus of elasticity was determined from the stress-strain curve. Five test pieces from each group were measured, and their arithmetic mean was taken as the tensile modulus of elasticity of the membrane.
[0116] <Membrane crystallinity>
[0117] For the aforementioned polyolefin films 1 to 6, rectangular test pieces of 25 mm × 15 mm (with arbitrary side orientations) were collected. Additionally, for each polyolefin film 1 to 6, an electron beam irradiation device (LB1036, manufactured by EYE Electron Beam Co., Ltd.) was used. After irradiating the electron beam with accelerating voltage and irradiation dose varying according to Table 1, rectangular test pieces of 25 mm × 15 mm (with arbitrary side orientations) were collected. The obtained test pieces were attached to the aluminum sample holder of an X-ray diffraction apparatus (Rigaku Electric Co., Ltd. 4036A2) with the film thickness direction as the normal direction to the sample holder surface. Using CuKa lines (with a Ni filter) as the X-ray source, and under output conditions of 40 kV-30 mA, the diffraction peaks were measured by reflection method using continuous 2θ-θ scanning while changing the incident angle of the X-rays. It should be noted that the measurement conditions were as follows, with measurements taken at 5 randomly selected locations on the sample.
[0118] • Measurement range (2θ): 5–60°
[0119] • Measurement step size (2θ): 0.05°
[0120] • Cumulative time: 2 seconds
[0121] For the diffraction peaks obtained by measurement, the peaks from crystalline components and the peaks from amorphous components are separated by analysis software (JADE5.0, MDI). The crystallinity is calculated from the peak area of each component using the following formula, and the arithmetic mean of the peaks is taken as the crystallinity.
[0122] Crystallinity (%) = Peak area of crystalline components × 100 / (Peak area of crystalline components + Peak area of amorphous components)
[0123] The results are shown in Table 2.
[0124] [Table 2]
[0125] Table 2
[0126]
[0127] <Registration accuracy>
[0128] In each embodiment and comparative example, starting from the state where the registration accuracy of each color is confirmed by aligning the crosshairs (dragonflies) with the same position during printing, printing continues without adjustment. For the printed matter after 30 seconds, the distance between the red crosshairs (dragonflies) and the white crosshairs (dragonflies) that are furthest apart from the red crosshairs (dragonflies) is measured (the distance between dragonflies). The smaller the distance between dragonflies, the better the registration accuracy; if it is less than 0.3 mm, the registration accuracy is evaluated as good.
[0129] <Seamlessness>
[0130] Using a bar coater No. 6, a diluted solution of dry lamination adhesive A-953 / A-93 (manufactured by Mitsui Chemicals Co., Ltd.) diluted with ethyl acetate to a non-volatile content of 50% by mass was applied to the ink of the printed materials obtained in the various examples and comparative examples, and dried using hot air. The dried weight of the coated adhesive was 2.3 g / cm³. 2 The polyolefin film was laminated in 7 layers onto the printed material coated with the above-mentioned adhesive using a calendering roller (Matsumoto Machinery Co., Ltd.), and cured at 40°C for 3 days to obtain the laminate.
[0131] Use a cutting tool to collect 15mm wide strips of test material from the resulting laminate. According to JIS K 6854-2:1999, standard name adhesives—test method for peel strength—part 2: 180° peel, perform a 180° peel test using a tensile testing machine at a load speed of 200mm / min to determine the peel strength between the ink and polyolefin films 1-6. If the peel strength is 1N / 15mm, it is considered to have good adhesion.
[0132] <Bag breakage caused by bag dropping>
[0133] Two rectangular test pieces, each 570 mm long and 360 mm wide, were taken from the laminate prepared by the above method. These were overlapped with polyolefin film 7 facing each other. Using a heat-sealing tester (TESTER SANGYO Co., Ltd.), the perimeters in three directions were sealed with a width of 10 mm under a pressure of 0.1 MPa. After filling the laminations with 10 kg of rice, the remaining perimeter in the same manner was sealed to create a packaging bag containing the rice.
[0134] Each bag containing rice was dropped three times from heights of 0.5m, 1.0m, and 1.5m in the longitudinal (perpendicular to the length direction), transverse (perpendicular to the width direction), and horizontal (horizontal in the length x width plane) directions, respectively. The presence or absence of bag breakage was investigated. A bag that did not break in all three drops was rated as good; a bag that broke at least once was rated as unacceptable. If no breakage was detected at a height of 0.5m, the bag breakage was considered suppressed.
[0135] [Example 1]
[0136] The following printing plate is placed on the first cylinder of a center-press printing press (CI-8, COMEXI Corporation). The printing plate is a horizontal (width direction): 1,070 mm, vertical (printing direction): 674 mm, without a horizontal plate (TAN-E, Toray Industries, Inc.), and has a cross mark (dragonfly) with a line thickness of 0.1 mm at a position 50 mm from each end of the plate in the printing direction: center and width direction. The following printing plates are respectively placed on the 6th and 7th cylinders of the aforementioned center-press printing press. These printing plates are horizontal (width direction): 1070 mm; vertical (printing direction): 674 mm. They are non-horizontal plate printing plates (TAN-E, Toray Industries, Inc.). Furthermore, the plates have a 100% solid line portion at the center, with a width direction of 900 mm and a vertical (printing direction) of 500 mm. In the printing direction (center) and at a distance of 50 mm from each end of the plate in the width direction, there are crosshairs (dragonflies) with a line thickness of 0.1 mm for registration accuracy confirmation. Red ink obtained by the aforementioned method is placed on the 1st cylinder, and white ink 1 obtained by the aforementioned method is placed on the 6th and 7th cylinders.
[0137] Using the corona treatment device attached to the printing press, corona irradiation was performed on the polyolefin film 1 as the substrate under the condition of irradiation intensity of 8.00kW. The ink feed rate of the first roller was 5%, the ink feed rate of the sixth and seventh rollers was 40%, the temperature setting of the cooler for the impression cylinder was 25°C, and the temperature setting of the cooler for the oscillating roller and ink tank was 28°C. Using T414 (manufactured by Kinyo Co., Ltd., thickness 1.95mm) for the blanket, red and white inks were applied at a speed of 100m / min using a wet-on-wet printing method. After full ink printing, the ink was cured by irradiating it with an electron beam irradiation device attached to the printing press under the conditions of accelerating voltage of 80kV and irradiation dose of 40kGy, thus obtaining the printed material.
[0138] The results obtained by evaluating the printed materials using the aforementioned method are shown in Table 3. In Example 1, the registration accuracy and fit were both good, and no bag breakage was found, indicating a good result.
[0139] [Examples 2-4]
[0140] The polyolefin film shown in Table 3 was used instead of polyolefin film 1, and the printed material was obtained using the same method as in Example 1. The results of the evaluation of the obtained printed material using the aforementioned method are shown in Table 3. In Examples 2-4, a higher tensile modulus resulted in better registration accuracy. All samples showed good adhesion, and no bag breakage was found, indicating good performance.
[0141] [Examples 5-8]
[0142] The accelerating voltage of the electron beam irradiation was changed as shown in Table 3. Otherwise, the printed material was obtained using the same method as in Example 1. The results obtained by evaluating the printed material using the aforementioned method are shown in Table 3. In Examples 5-8, the registration accuracy was good, and the higher the accelerating voltage, the better the seal. On the other hand, regarding bag breakage, there is a tendency for lower accelerating voltages to be better.
[0143] [Examples 9-11]
[0144] The polyolefin film shown in Table 3 was used instead of polyolefin film 1, and the printed material was obtained by the same method as in Example 8. The results of the evaluation of the obtained printed material by the aforementioned method are shown in Table 3. In Examples 9-11, the higher the tensile modulus, the better the registration accuracy. The seal was good, and no bag breakage was found, which is good.
[0145] [Examples 12-15]
[0146] The electron beam irradiation dose was changed as shown in Table 4, and the printed material was obtained using the same method as in Example 1. The results obtained by evaluating the printed material using the aforementioned method are shown in Table 4. In Examples 12-15, the registration accuracy was good, and the higher the irradiation dose, the better the seal. On the other hand, regarding bag breakage, there was a tendency for lower irradiation doses to be better.
[0147] [Examples 16-21]
[0148] The white ink shown in Table 4 was used instead of white ink 1, and the printed matter was obtained by the same method as in Example 1. The results obtained by evaluating the resulting printed matter using the aforementioned method are shown in Table 4. In Examples 16-21, there was a tendency for good registration accuracy when using inks containing anionic surfactants, and for less bag breakage when using inks containing urethane acrylates. The peel strength was good in all cases.
[0149] [Comparative Examples 1-2]
[0150] The polyolefin film shown in Table 4 was used instead of polyolefin film 1, and the printed material was obtained by the same method as in Example 1. The results of the evaluation of the obtained printed material by the aforementioned method are shown in Table 4. Comparative Example 1 used a film with a tensile modulus of elasticity in the MD direction of less than 200 MPa, resulting in poor registration accuracy. Comparative Example 2 used a film with a tensile modulus of elasticity in the MD direction of greater than 1,000 MPa, resulting in easy bag breakage.
[0151] [Table 3]
[0152]
[0153] [Table 4]
[0154]
[0155] It should be noted that in Tables 3 and 4, "crystallization degree after electron beam irradiation (%)" refers to the crystallinity after electron beam irradiation under the conditions of irradiation dose (kGy) and accelerating voltage (kV) recorded in the "Electron beam irradiation conditions" item of the table.
Claims
1. A method for manufacturing printed matter, comprising, in sequence: The transfer process, among which, The ink is transferred onto a polyolefin film with a tensile modulus of 200 MPa to 1,000 MPa in the MD direction by a center imprinting printing method. as well as The curing process involves irradiating the ink with an electron beam to cure the ink. The polyolefin film contains more than 10% by mass of polyethylene resin and less than 90% by mass of polypropylene resin.
2. The method for manufacturing printed matter as described in claim 1, wherein, The thickness of the polyolefin film is more than 20 μm and less than 60 μm.
3. The method for manufacturing printed matter as described in claim 1 or 2, wherein, The ratio (C2 / C1) of the crystallinity C2 of the polyolefin film after electron beam irradiation under the conditions of accelerating voltage 110kV and irradiation dose 40kGy is 0.8 or more and 1.2 or less.
4. The method for manufacturing printed matter as described in claim 1 or 2, wherein, The crystallinity C2 of the polyolefin film after electron beam irradiation under the conditions of accelerating voltage 110kV and irradiation dose 40kGy is above 20% and below 50%.
5. The method for manufacturing printed matter as described in claim 1 or 2, wherein, The content of the crystal nucleating agent in the polyolefin film is less than 0.01% by mass.
6. The method for manufacturing printed matter as described in claim 1 or 2, wherein, In the curing process, electron beam irradiation is performed under the conditions of accelerating voltage of 70kV to 90kV and irradiation dose of 20kGy to 60kGy.
7. The method for manufacturing printed matter as described in claim 1 or 2, wherein, The ink contains anionic surfactants.
8. The method for manufacturing printed matter as described in claim 1 or 2, wherein, The ink contains urethane (meth) acrylate.
9. The method for manufacturing printed matter as described in claim 1 or 2, wherein, In the transfer process, ink is transferred by lithographic printing.
10. A method for manufacturing a laminate, comprising the steps of manufacturing a printed matter by the method of any one of claims 1 to 9 and laminating an unstretched polyolefin film onto the printed matter.
11. The method for manufacturing a laminate as described in claim 10, wherein, The tensile modulus of the unstretched polyolefin film is between 50 MPa and 400 MPa.
12. The method for manufacturing a laminate as described in claim 10 or 11, wherein, The thickness of the unstretched polyolefin film is between 30 μm and 100 μm.
13. A method for manufacturing a packaging bag, comprising: a step of producing a laminated body by the method for manufacturing a laminated body according to any one of claims 10 to 12; and a step of making a bag from the laminated body.
Citation Information
Patent Citations
Active energy ray-curable ink composition for offset printing and production method of printed matter using the same
JP2015168730A
Active energy ray-curable composition, active energy ray-curable ink, and printed matter
JP2020033465A
Method for producing printed material and printing machine
WO2018163941A1
Method for manufacturing printed matter
CN113557144A
Multicolor printing method
JP2005103925A
